THU0426 Ethnic variation in systemic sclerosis morbidity and mortality. (12th June 2018) - Al-Sheikh, H.; Ahmad, Z.; Johnson, S.R.
Abstract : Background: Systemic sclerosis (SSc) is an uncommon connective tissue disease characterised by pathological skin thickening and can involve multiple internal organs. Ethnic variations in SSc have been reported in clinical manifestations, severity of the disease as well as survival. Objectives: Our aim was to compare the survival and disease manifestations across ethnicity among SSc patients. Methods: The Toronto Scleroderma Program is the largest single-centre, multiethnic, longitudinal SSc cohort in Canada. Patients are followed every 6 to 12 months using a standardised protocol. Patients who fulfilled the American College of Rheumatology-European League Against Rheumatism classification criteria for SSc and are 16 years of age or older were included in our retrospective cohort study. The study period was 1970–2017. Ethnicity was self-reported and was categorised as: Caucasian, African-American, Hispanic, Arab, East-Asian, First Nations or Persian. The primary outcome was the time from diagnosis to death from all causes. Secondary outcomes were differences in disease duration, SSc subtype, clinical manifestations, and serology. Survival probabilities and median survival times were determined using Kaplan-Meier survival curves. Cox proportional hazard models were used to estimate adjusted survival. Results: 1005 subjects were evaluated, the majority of whom were Caucasian (n=745 (74%), African-American n=58 (6%)), South Asian (n=69 (7%)), and East Asian (n=80 (8%)). Compared to Caucasians, East Asians less frequently had calcinosis (29% versus 9%, p=0.002), and esophageal dysmotility (88% versus 69%, p=0.002); African-Americans more frequently had interstitial lung disease (31% versus 53%, p=0.007); and First Nation subjects more frequently had diffuse cutaneous disease (35% versus 56%, p=0.02) and diabetes (5% versus 33%, p=0.03). There were no differences across ethnicities in the prevalence of pulmonary hypertension, renal crisis, or digital ulcers. We found no difference in the short-term survival across ethnicities. However, in the long-term, there was trend for Hispanic subject to have better survival (81.3% (95%CI 63, 100), while First Nations (58.3% (95%CI 25, 100) and South Asian subjects (52.6% (95%CI 32, 87) had worst survival at 15 years and 20 years, respectively. East Asians appear to have the longest median survival time 43.3 years. Conclusions: Ethnic variations in disease SSc disease manifestations are observed. However, in the setting of a universal health care system, this does not result in significant differences in survival. Disclosure of Interest: None declared